Under Pressure to Achieve? The Impact of Type and Style of Task Instructions on Student Cheating - Pulfrey, Caroline Julia; Vansteenkiste, Maarten; Michou, Aikaterina (Frontiers in Psychology, 2019)
Combining principles of Achievement Goal Theory, which maintains that performance goals play a key role in individuals’ likelihood of cheating, and Self-Determination Theory, which highlights the importance of individuals’ reasons for adopting achievement goals, we examined whether the combination of experimentally inducing a performance-approach (relative to mastery-approach) goal, combined with controlled or pressured (instead of autonomous and volitional) reasons for goal adoption may incite cheating. In two experiments carried out with university students, one classroom based (N = 164) and one laboratory (N = 160), we manipulated the type of induced goal (performance- vs. mastery-approach) and style of introducing the goal (i.e., controlling versus autonomy-supportive), hypothesizing that the least behaviorally observed cheating would occur in a context promoting mastery-approach goals in an autonomy-supportive way. The dependent variables in both studies consisted of two set of exercises, both including questions that could only be solved by cheating. Results of Poisson regression analyses revealed that in both studies the least cheating in the first set of exercises occurred in the autonomy-supportive/mastery-approach condition, indicating that this induced goal complex has the greatest potential to restrain academic dishonesty in the short-term. Interaction effects with self-enhancement value adherence revealed that the cheating inhibitory effects of this induced goal complex was less effective for those who value power and achievement.